2017
DOI: 10.1093/gerona/glx044
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Follow-Up After a 2-Year RCT with Vitamin D and Exercise: Effects on Falls, Injurious Falls and Physical Functioning Among Older Women

Abstract: BackgroundBoth exercise and vitamin D are recommended means to prevent falls among older adults, but their combined effects on fall-induced injuries are scarcely studied.MethodsA 2-year follow-up of a previous 2-year randomized controlled trial with vitamin D and exercise (Ex) of 409 older home-dwelling women using a factorial 2 × 2 design (D−Ex−, D+Ex−, D−Ex+, D+Ex+). Besides monthly fall diaries, femoral neck bone mineral density (fn-BMD), and physical functioning were assessed at 1 and 2 years after the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
(49 reference statements)
0
41
0
Order By: Relevance
“…The present systematic review included in total 31 interventions (participants in total n = 4739), and their characteristics are summarized in Table 2 . Twenty-four interventions reported both the fall rate and fall risk while three interventions investigated the fall risk only [ 50 , 84 , 85 ] and four interventions reported only the fall rate [ 83 , 86 , 87 ]. The mean age of the included participants was 74.1 ± 4.3 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present systematic review included in total 31 interventions (participants in total n = 4739), and their characteristics are summarized in Table 2 . Twenty-four interventions reported both the fall rate and fall risk while three interventions investigated the fall risk only [ 50 , 84 , 85 ] and four interventions reported only the fall rate [ 83 , 86 , 87 ]. The mean age of the included participants was 74.1 ± 4.3 years.…”
Section: Resultsmentioning
confidence: 99%
“… Trombetti et al [ 88 ] Yes Yes Yes Yes Yes Unclear The control group was a delayed intervention control group that started the same implemented intervention during the 6 months of follow-up. Uusi-Rasi et al [ 87 ] Yes Unclear Yes Yes Unclear Unclear Weerdesteyn et al [ 100 ] Yes Unclear Unclear Yes Yes Unclear Half of the intervention group was not randomly assigned. The follow-up started from the point of group assignment.…”
Section: Resultsmentioning
confidence: 99%
“…If a vitamin D deficiency or osteoporosis is diagnosed, supplementation with vitamin D and calcium should be considered. The relevance of vitamin D supplementation in fall and injury prevention is currently the subject of controversy in the scientific community, but the benefit of (moderate) vitamin D supplementation has been demonstrated in several recently published, randomized, controlled trials …”
Section: Discussionmentioning
confidence: 99%
“…The relevance of vitamin D supplementation in fall and injury prevention is currently the subject of controversy in the scientific community, but the benefit of (moderate) vitamin D supplementation has been demonstrated in several recently published, randomized, controlled trials. 24,25 Recent studies in which the effectiveness of fall prevention programs was assessed, revealed that interventions that cover multiple components are the most promising for preventing falls. 26 This is not surprising, as falls are a geriatric syndrome, and the causes for these are mostly multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that exercise training can reduce the severity of falls [ 22]. This benefit was partly maintained after cessation of the exercise intervention, despite the fact that physical activity had returned to baseline and did not differ from the non-training counterparts anymore [23][24][25]. However, all exercise trials do not support a reduction in falls incidence [ 26,27].…”
Section: Discussionmentioning
confidence: 89%